DERAJAT KECEMASAN DAN AKTIVITAS FISIK MAHASISWA PENDIDIKAN JASMANI DI MASA PANDEMI - Syafriansyah Syafriansyah; Ahmad Atiq; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2021)
AbstractThe problem in this study is to determine the level of anxiety and the level of student physical activity during the pandemic. The problem is that every student in the physical education study program during the pandemic experiences a change in the learning process from face to face to online.This research method is a quantitative research in the form of research using a survey by giving a questionnaire. In the form of a questionnaire has all the preparation of the questions developed, namely google from with a sample of 32 students of physical education study program. The results of the research that can be presented are: Research on the degree of student anxiety during the pandemic has answered yes 325 points with a percentage of 52% and physical activity during pandemic has answered no 302 points with a percentage of 48%. Research on student physical activity has 3 classifications, namely 4 people are in the low category with a percentage of 33 % with a lot of activity 103 meters and a moderate category of 4 students with a percentage of 33% a lot of activity 2503 meters and a high category with a percentage of 44% with a physical activity of 4690 meters, it can be concluded that students have a slight weakness in the degree of anxiety and good physical activity even during the pandemic like this.Keywords: Anxiety, Physical Activity